2015
DOI: 10.15407/ujpe60.09.0960
|View full text |Cite
|
Sign up to set email alerts
|

Physical Nature of Hydrogen Bond

Abstract: PHYSICAL NATURE OF HYDROGEN BOND PACS 82.30.RsThe physical nature and the correct definition of hydrogen bond (H-bond) are considered. The influence of H-bonds on the thermodynamic, kinetic, and spectroscopic properties of water is analyzed. The conventional model of H-bonds as sharply directed and saturated bridges between water molecules is incompatible with the behavior of the specific volume, evaporation heat, and self-diffusion and kinematic shear viscosity coefficients of water. On the other hand, it is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…5 and 6 showed that the surfaces of the pressure-temperature dependences of the derivative (𝜕𝑉 /𝜕𝑇 ) 𝑃 for water and argon are qualitatively similar in the intervals of relative temperatures 0.56 < 𝑇 /𝑇 𝑐 < 0.7 and pressures 0.02 < 𝑃/𝑃 𝑐 < 20. This fact confirms the validity of the principle of corresponding states for water and argon and is consistent with the conclusions of works [38][39][40].…”
Section: Temperature-pressure Dependences Of (𝜕𝑉 /𝜕𝑇 ) 𝑃supporting
confidence: 92%
See 1 more Smart Citation
“…5 and 6 showed that the surfaces of the pressure-temperature dependences of the derivative (𝜕𝑉 /𝜕𝑇 ) 𝑃 for water and argon are qualitatively similar in the intervals of relative temperatures 0.56 < 𝑇 /𝑇 𝑐 < 0.7 and pressures 0.02 < 𝑃/𝑃 𝑐 < 20. This fact confirms the validity of the principle of corresponding states for water and argon and is consistent with the conclusions of works [38][39][40].…”
Section: Temperature-pressure Dependences Of (𝜕𝑉 /𝜕𝑇 ) 𝑃supporting
confidence: 92%
“…The pressure-temperature dependences of the derivative (𝜕𝑉 /𝜕𝑇 ) 𝑃 for water and argon were analyzed with regard for the principle of corresponding states [26]. Note that, according to works [38][39][40], despite a substantial difference between the properties of water and argon, there exists a temperature interval, at 𝑇 ≪ 𝑇 𝑐 , where the principle of corresponding states can be applied.…”
Section: Temperature-pressure Dependences Of (𝜕𝑉 /𝜕𝑇 ) 𝑃mentioning
confidence: 99%
“…5 and 6, the plotted surfaces are qualitatively similar. This fact confirms the validity of the principle of corresponding states in the indicated temperature and chemical potential inter-vals for water and argon, and is in agreement with the conclusions of works [25,[28][29][30].…”
Section: (𝑇 𝜇)-Dependences Of − (𝜕𝑉 /𝜕𝑃 ) 𝑇supporting
confidence: 92%
“…To verify the applicability of the principle of corresponding states [26,27], we performed a comparative analysis of the (𝑇, 𝜇)-dependences of the derivative − (𝜕𝑉 /𝜕𝑃 ) 𝑇 for water and argon. It should be noted that, despite a significant difference between the properties of water and argon, nevertheless, according to [28][29][30], there exists a region at 𝑇 < 𝑇 𝑐 (𝑇 𝑐 is the critical temperature), where the principle of corresponding states is applicable. A similar conclusion about the existence of the region of thermodynamic similarity was made in work [25] when analyzing the (𝑇, 𝑝)-dependences of the thermodynamic coefficient (𝜕𝑉 /𝜕𝑇 ) 𝑃 .…”
Section: (𝑇 𝜇)-Dependences Of − (𝜕𝑉 /𝜕𝑃 ) 𝑇mentioning
confidence: 99%